VD_FINDINFO Arrêt / 2025 / 614 vom 4. August 2025 - VD Tribunal cantonal (2025)
RENTE D'INVALIDITÉ, ÉVALUATION DE L'INCAPACITÉ DE TRAVAIL, REJET DE LA DEMANDE | 28 al. 1 LAI, 4 al. 1 LAI, 16 LPGA, 8 LPGA